Helmet use in equestrian athletes: opportunities for intervention - Grimes Stanfill, A.; Wynja, K.; Cao, X.; Prescott, D.; Shore, S.; Baughman, B.; Oddo, A.; Tsao, J. W. (Concussion, 2020)
Background: Equestrian athletes (horse riders) are at high risk for head injury, including concussions. Materials & methods: Adults riders were recruited via social media posting to complete a branching survey collecting data on demographics, riding experience, helmet use, injury history and concussion symptom knowledge. Results are reported as frequencies and percentages, with associations tested using chi-square with significance level p < 0.05. Results: Of the 2598 subjects, about 75% reported always wearing a helmet. Of those who did not, the most common reasons were that helmets are unnecessary (57.4%) or do not fit well (48.6%). Many indicated improper storage conditions and/or did not follow manufacturer`s replacement recommendations. Most (75.4%) reported a high level of comfort with recognizing concussion signs, with half experiencing a prior head injury. Conclusion: This information suggests opportunities for intervention to improve helmet use through increased fit, while the responses indicate a need for further education on proper helmet use.